Catalyst‐ and Initiator‐Free Radical Addition under Mild Conditions: A Macromolecular Conjugation Tool. Issue 15 (15th February 2018) - Autissier, Laurent; Mabrouk, Kamel; Chendo, Christophe; Guillaneuf, Yohann; Rollet, Marion; Charles, Laurence; Gigmes, Didier; Trimaille, Thomas
Abstract: A catalyst/initiator‐free radical addition reaction performed under mild conditions (water, 30 °C) with high yields is reported for the first time. This reaction implies simple pH‐mediated alkoxyamine dissociation followed by addition onto olefinic substrates. The versatility and relevance of this selective reaction for macromolecular conjugation and engineering are shown through the syntheses of block copolymers, as well as hydrogels containing in situ‐loaded proteins, which could retain biological activity. This contrasts with standard thermal radical conditions that lead to complete protein inactivation. Abstract : Cata‐less : The first catalyst‐free and initiator‐free radical addition under mild conditions is presented, offering versatile syntheses of block copolymers and in situ‐loaded protein hydrogels.